Resistance to QoI fungicides Is widespread in brazilian populations of the wheat blast pathogen magnaporthe oryzae - Castroagudin, Vanina L. [UNESP]; Ceresini, Paulo C. [UNESP]; Oliveira, Samanta C. de [UNESP]; Reges, Juliana T. A. [UNESP]; Maciel, Joao L. N.; Bonato, Ana L. V.; Dorigan, Adriano F. [UNESP]; McDonald, Bruce A. (Amer Phytopathological Soc, 2015)
Wheat blast, caused by Magnaporthe oryzae, is an important disease across central and southern Brazil. Control has relied mainly on strobilurin fungicides (quinone-outside inhibitors [Qols]). Here, we report the widespread distribution of Qol resistance in M. oryzae populations sampled from wheat fields and poaceous hosts across central and southern Brazil and the evolution of the cytochrome b (cyt b) gene. Sequence analysis of the cyt b gene distinguished nine haplotypes, with four haplotypes carrying the G143A mutation associated with Qol resistance and two haplotypes shared between isolates sampled from wheat and other poaceous hosts. The frequency of the G143A mutation in the wheat-infecting population increased from 36% in 2005 to 90% in 2012. The G143A mutation was found in many different nuclear genetic backgrounds of M. oryzae. Our findings indicate an urgent need to reexamine the use of strobilurins to manage fungal wheat diseases in Brazil.